Effect of yoga practice on cognitive functions among the patients of depression - Nitu Kumari,; Ishwar Dayal Gupta,; Dheeraj Jeph,; Anuradha Yadav,; Kavita Yadav,; Namit Garg,; Sai Sailesh Kumar Goothy,; Anita Choudhary, (Asian Journal of Medical Sciences, 2023)
Background: Decline in the cognitive functions is commonly observed in patients suffering with depression. Practicing yoga was reported to improve cognitive functions as well as manages depression. Aims and Objectives: The present study was undertaken to observe the effect of yoga practice on cognitive functions among the patients of depression. Materials and Methods: A total of 64 patients suffering with depression were recruited after obtaining written informed consent. Participants were randomly assigned to the interventional and control groups with 32 participants in each group. Digit span test (DST) was used to assess the cognitive functions of the participants at the baseline, after 1 month, and after 3 months of intervention. Yoga practice was administered as an adjunctive therapy to the interventional group for 3 months of period. No intervention was administered to the control group. Unpaired Student’s “t”-test and repeated measure ANOVA test were applied and P<0.05 was considered as statistically significant. Results: The forward, backward, and total DST scores were not significantly different between the interventional and control groups at the baseline as well as after 1 month. Whereas, a statistically significant improvement after 3 months of yoga intervention in the forward (P<0.001), backward (P<0.05), and total (P<0.001) DST scores was observed when the interventional group was compared with the control group. A statistically significant improvement was observed in the interventional group even after 1 month of yoga practice in forward (P<0.001) and total (P<0.05) DST scores, while in backward DST scores, statistically significant improvement was observed after 3 months. Conclusion: The study results support improvement in the cognitive functions followed by yoga practice in patients suffering from depression within a short period of time. The study recommends the implication of yoga practice as an adjunctive therapy in the management of depression.